Servant Leadership and Influence on Teacher Professional Development in Islamic Boarding Schools - Nur Efendi (Pondok Pesantren As-salafiyah Asy-syafi'iyyah, 2024)
This study investigates the influence of servant leadership on teacher professional development in an Islamic boarding school in Tulungagung. The research addresses how leadership practices shape professional learning, how they affect teacher development outcomes, and how both elements interact within the institutional context. A qualitative case study design was employed to explore in-depth perspectives from the kyai, teachers, and administrative staff. Data were collected through semi-structured interviews, observations of daily educational activities, and document analysis, followed by thematic analysis. The findings indicate that servant leadership creates a supportive, value-oriented environment that encourages continuous professional growth through mentoring, collaboration, and reflective practice. Teachers demonstrate improved competence in instructional strategies, classroom management, and integration of religious values into teaching. Professional development outcomes are reflected in increased engagement, confidence, and participation in learning activities. The study also reveals a dynamic and interconnected relationship in which leadership values shape teacher development, professional practices enhance instructional quality, and feedback informs leadership refinement. These findings highlight the critical role of servant leadership in sustaining effective teacher development within Islamic boarding school contexts.